2017
DOI: 10.1136/vetreccr-2016-000392
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous broncho‐oesophageal arteries and peripheral systemic‐to‐pulmonary connections in an asymptomatic puppy

Abstract: A clinically healthy four-month-old puppy had a grade 2/6 left basilar, continuous heart murmur and was presented for further evaluation. Echocardiography revealed multiple small diastolic colour signals around the main right pulmonary artery. Mild pulmonary overcirculation and left ventricular enlargement were observed on thoracic radiography. Contrast enhanced CT with angiography revealed anomalous broncho-oesophageal arteries with peripheral pulmonary shunting, consistent with systemic-to-pulmonary connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Continuous murmurs are usually heard in PDA and APW ( 2 , 4 ), generally at the base and apex ( 4 , 27 ). All previous cases of BEA hypertrophy had various grades of left-sided murmur, either apical or basal ( 11 , 14 , 15 , 17 ); however, no study has reported BEA hypertrophy with a right basal murmur. In previous reports regarding BEA hypertrophy, shunt insertion locations were the proximal left pulmonary artery, between the aorta and the pulmonary artery, and the proximal RPA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Continuous murmurs are usually heard in PDA and APW ( 2 , 4 ), generally at the base and apex ( 4 , 27 ). All previous cases of BEA hypertrophy had various grades of left-sided murmur, either apical or basal ( 11 , 14 , 15 , 17 ); however, no study has reported BEA hypertrophy with a right basal murmur. In previous reports regarding BEA hypertrophy, shunt insertion locations were the proximal left pulmonary artery, between the aorta and the pulmonary artery, and the proximal RPA.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of L-to-R shunts depends on their size and the blood flowing through them ( 1 ). The types of L-to-R shunts include patent ductus arteriosus (PDA) ( 2 , 3 ), aortopulmonary window (APW) ( 4 7 ), L-to-R arteriovenous fistulae ( 8 ), arteriovenous shunts ( 9 ), and various atypical L-to-R shunts ( 10 – 17 ). Bronchoesophageal artery (BEA) hypertrophy, also referred to as an aberrant BEA, is a relatively rare type of L-to-R shunt in dogs ( 10 , 11 , 14 , 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations